The Counter-Conduct of Medieval Hermits - Christopher Roman (Foucault Studies, 2016)
The hermit posed a challenge to a medieval Church that emphasized rule, order, and discipline since oversight of their life could be virtually non-existent. The writings of Richard Rolle, hermit, negotiates the space between Foucauldian exomolgesis and exoagouresis as Rolle strove to articulate the identity of the hermit without any kind of church endorsement. As well, he forged his life out of a struggle with concepts of medieval sin, specifically Pride, which placed him in a queer position in terms of relationships with his surrounding community. His way of life was highly influential in his local community, however, and, through manuscript dissemination, beyond. Because he experienced mystical visions without church oversight, his eremitic life and example inspired a movement toward lay, affective piety in the later Middle Ages. The hermit, in his case, challenges the medieval Church’s hierarchy in that hermits practice a form of living at a local level, placing them in dangerous, sometimes heretical, positions that force the Church to either absorb their practices or suppress them.